2020
DOI: 10.3139/120.111581
|View full text |Cite
|
Sign up to set email alerts
|

Determination of readiness for laying based on material moisture, corresponding relative humidity, and water release

Abstract: The moisture content of the subfloor has to be determined before installation to avoid damage to the floor covering. Only if readiness for layering is reached, can an installation without damage be expected in all cases. In general, three approaches exist to measure residual water content: determination of moisture content, determination of water release, or determination of the corresponding relative humidity. All three approaches are tested under laboratory conditions at eight screed types including two samp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 6 publications
0
2
1
Order By: Relevance
“…Furthermore, with respect to the RH after 15 minutes, the limit of 75 % RH is also reached after around 12 hours. These results do not correspond well to past results on screeds [5], where a water transport of only about 1.25 g/m²/h was found that corresponded with a relative humidity of 85 % and thus, laying readiness. The results shown here indicate that the measurements of water release provide interesting information on the drying behaviour of a material.…”
Section: Conventional Results On Slu Dryingcontrasting
confidence: 99%
See 1 more Smart Citation
“…Furthermore, with respect to the RH after 15 minutes, the limit of 75 % RH is also reached after around 12 hours. These results do not correspond well to past results on screeds [5], where a water transport of only about 1.25 g/m²/h was found that corresponded with a relative humidity of 85 % and thus, laying readiness. The results shown here indicate that the measurements of water release provide interesting information on the drying behaviour of a material.…”
Section: Conventional Results On Slu Dryingcontrasting
confidence: 99%
“…For the CRH method, chemically bound water does not contribute to the result, as no water vapour pressure is exerted. Last, to fully evaluate the laying readiness, the water release from the surface might be considered [5]. For regular cementitious screeds, a release of up to 30 g/m²/d (1.25 g/m 2 /h) was found to coincide with a relative humidity within the material of 85 % that marks the limit between unbound water in capillaries and the cement gel structure [5].…”
Section: Introductionmentioning
confidence: 99%
“…295 K). On the following morning, the samples were stored in a ventilated climate chamber at an ambient relative humidity of % RH and an ambient temperature of K. Further details are discussed in [ 31 , 67 ].…”
Section: Methodsmentioning
confidence: 99%